2021
DOI: 10.26444/aaem/136572
|View full text |Cite
|
Sign up to set email alerts
|

Is job seniority a protective factor against anxiety among midwives during the SARS-CoV-2 pandemic?

Abstract: Is job seniority a protective factor against anxiety among midwives during the the SARS-CoV-2 pandemic? Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to Geneviève Gariépy, social support significantly impacts the prevention of depression in the elderly. The source, which is associated the most with the prevention of depression, were spouses, followed by friends [26]. According to Tengku Mohd TAM et al, good overall social support, having a spouse or partner, living with family, more frequent contact with loved ones, support from family and satisfaction with social support, are associated with fewer depressive symptoms in community-dwelling older adults in Asia [27].…”
Section: Discussionmentioning
confidence: 99%
“…According to Geneviève Gariépy, social support significantly impacts the prevention of depression in the elderly. The source, which is associated the most with the prevention of depression, were spouses, followed by friends [26]. According to Tengku Mohd TAM et al, good overall social support, having a spouse or partner, living with family, more frequent contact with loved ones, support from family and satisfaction with social support, are associated with fewer depressive symptoms in community-dwelling older adults in Asia [27].…”
Section: Discussionmentioning
confidence: 99%
“…( 2020 ) found that symptoms of depression and anxiety were more common in Indian healthcare workers (including nurses and physicians) with less than ten years of work experience, whereas Zhu et al ( 2020 ) found that having over ten years of seniority was associated with acute stress, depression and anxiety symptoms amongst healthcare workers in Wuhan, China. In contrast, Gotlib et al ( 2021 ) stressed that professional experience had no effect on level of anxiety among Polish midwives. Finally, with regard to profession, nurses were found more likely to have anxiety symptoms compared with physicians and other medical workers (Lai et al, 2020 ; Si et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
“…A recent Indian study reported the protective factor for anxiety of healthcare workers with more than 20 years of work experience [ 18 ]. In contrast, the length of professional experience did not correspond to the level of anxiety in a group of Polish midwives during the SARS-CoV-2 pandemic [ 19 ]. In an Iranian study during the COVID-19pandemic, healthcare workers who had higher depression and distress, and had lower job satisfaction [ 20 ].…”
Section: Introductionmentioning
confidence: 99%